Cannabidiol Suppresses Angiogenesis and Stemness of Breast Cancer Cells by Downregulation of Hypoxia-Inducible Factors-1α - Min Jee Jo (MDPI AG, 2021)
To assess the effect of Cannabidiol (CBD) on the angiogenesis and stemness of breast cancer cells as well as proliferation. Methods: mRNA level and the amount of protein of vascular endothelial growth factor (VEGF) were determined by qRT-PCR and ELISA. The angiogenic potential of breast cancer cells under hypoxic conditions was identified by the HUVEC tube formation assay. The degradation of HIF-1α by CBD and the Src/von Hippel–Lindau tumor suppressor protein (VHL) interaction were assessed by a co-immunoprecipitation assay and Western blotting. To identify the stemness of mamospheres, they were evaluated by the sphere-forming assay and flow cytometry. Results: CBD can suppress angiogenesis and stem cell-like properties of breast cancer through Src/VHL/HIF-1α signaling. CBD may potentially be utilized in the treatment of refractory or recurrent breast cancer.